Simplified segmental scleral buckling without localization and cryopexy: A retrospective comparison with conventional segmental scleral buckling - Pei-Hsuan Lin; Yi-An Lee; Lu-Chun Wang (Taiwan Journal of Ophthalmology)
PURPOSE: The aim of this study was to propose a simplified segmental scleral buckling (SSSB) technique that does not require break localization for less-experienced vitreoretinal surgeons. MATERIALS AND METHODS: This retrospective study compared the clinical results of 46 conventional and 23 SSSB (conventional segmental SB [CSSB] and SSSB, respectively) procedures in a tertiary referral retinal center in Taiwan between 2008 and 2019. In the CSSB group, breaks were localized during surgery. In the SSSB group, a wider sponge band and a longer scleral buckle were used to maximize the chances of sealing the retinal breaks based on the preoperative fundus examination findings and to minimize the positioning error caused by cyclotorsion, without performing indirect ophthalmoscopy. The primary outcome was assessed after 6 months. Patient characteristics, surgical parameters, and outcomes were compared between groups. The main outcomes were the duration of surgery, changes in visual acuity, primary success rate, rhegmatogenous retinal detachment recurrence rate, and the frequency of further laser photocoagulation. RESULTS: SSSB had a shorter duration than CSSB and was associated with more frequent use of longer and wider explants and need for further laser retinopexy. Both groups showed high primary success rates (95.65%). CONCLUSION: The primary success rates for the SSSB and CSSB groups were comparable and equally high. SSSB required laser retinopexy more frequently and was a shorter procedure.